House of Nails / Nor Idrwaty Idris ... [et al.] - Idris, Nor Idrwaty; Ahmad Nor, Norashikin; Md.Zain, Putri Siti Norhayati; Zaulkifli, Faznida; Salehuddin, Sharizatul Nazira; Zainudin, Azril Rizal (Faculty of Communication and Media Studies, 2004)
The main purpose in preparing the business plan is to fulfill needs among members of the company in making one business is continuous. Beside that, the purpose of business plan also to continue the maximum profit and to attract and accurate the number of sales. Besides that also, the purpose is to prove that native also can make a business and build one competitor organization that oriented profit. The development of business in Malaysia is more important with a wide of competitor.